Therapi Shiatsu terhadap Kecemasan Perempuan Menopause Post Op Ca. Mammae - Lisda Maria; Syerliza Febrianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine how effective shiatsu therapy is on the anxiety of post-op menopausal women. Mammary at Pusri Hospital. This research uses a quantitative method with a quasi-experimental pre and post-test design. The results showed that the mean value of anxiety in the treatment and control groups was 32. The results of bivariate analysis obtained a p-value = 0.000. In conclusion, shiatsu therapy was performed eight times in Menopausal Post Op Ca women. Mammae have a significant effect on reducing anxiety levels. Keywords: Menopause, Anxiety, Post Op Ca. Mammae, Shiatsu Therapy